On some investigations of alpha-conformable Ostrowski–Trapezoid–Grüss dynamic inequalities on time scales - Ahmed A. El-Deeb (Journal of Inequalities and Applications, 2023)
Abstract We prove new Ostrowski-type α-conformable dynamic inequalities and its companion inequalities on time scales by using the integration-by-parts formula on time scales associated with two parameters for functions with bounded second delta derivatives. When α = 1 $α =1$ , we obtain some well-known time-scale inequalities due to Ostrowski. As particular cases, we obtain new continuous and discrete inequalities.